2020
DOI: 10.1021/acs.estlett.0c00052
|View full text |Cite
|
Sign up to set email alerts
|

Release of Volatile Per- and Polyfluoroalkyl Substances from Aqueous Film-Forming Foam

Abstract: Research on per- and polyfluoroalkyl substances (PFASs) released from aqueous film-forming foams (AFFFs) has primarily focused on soil and groundwater contamination, or atmospheric transport. However, gas-phase PFAS release from AFFF has not been well examined. We investigated the presence of volatile PFASs in the headspace above agitated AFFF concentrate produced within the past two years using two analytical techniques. One method utilized polyurethane foam and XAD resin with liquid chromatography mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 58 publications
0
53
1
Order By: Relevance
“…63 A recent study evaluated the gas phase PFAS could release from agitated AFFF and concluded that PFOA was the most abundant PFAS detected in the headspace, followed by perfluorohexane and four other iodinated and ethenyl fluorocarbons. 64…”
Section: Introductionmentioning
confidence: 99%
“…63 A recent study evaluated the gas phase PFAS could release from agitated AFFF and concluded that PFOA was the most abundant PFAS detected in the headspace, followed by perfluorohexane and four other iodinated and ethenyl fluorocarbons. 64…”
Section: Introductionmentioning
confidence: 99%
“…In this comment, PFOA denotes the anionic species of the compounds, whereas PFOA-H denotes the protonated form. Note that Roth et al did not differentiate between PFOA and PFOA-H. 1 Roth et al sampled the AFFF headspace with thermal desorption (TD) tube and XAD/PUF samplers and analyzed them using gas chromatography with mass spectrometry (GC-MS) and by liquid chromatography with tandem MS (LC-MS/ MS), respectively. Roth et al also injected a methanolic standard of PFOA-H onto a TD tube for analysis by GC-MS.…”
mentioning
confidence: 99%
“…Roth et al did not report a molecular ion and only reported the retention time and fragmentation pattern for the PFOA-H directly injected onto the GC/MS. They observed mass-to-charge (m/z) 69 (CF 3 ), 119 (C 2 F 5 ), 131 (C 3 F 5 ), and 169 (C 3 F 7 ), 1,2 which are characteristic of several highly fluorinated subclasses (including fluorotelomer alcohols, perfluoroalkyl iodides, ethyl perfluoroalkane sulfonamides) and, thus, are not unique to PFOA-H/PFOA. 3,4 Moreover, the PFOA-H fragmentation pattern in Figure S3 of Roth et al does not match the NIST MS spectrum of PFOA-H. 5 In fact, in their Figure S3, perfluoro-1-heptene (PFHP) gave the best match compared to PFOA-H, which gave the sixth best match.…”
mentioning
confidence: 99%
See 2 more Smart Citations